Kesiapan perpustakaan Indonesia menyongsong MEA - Muhammad Riandy Arsin Siregar (IQRA`: Jurnal Ilmu Perpustakaan dan Informasi (e-Journal), 2016)
This article describes how to readiness in facing MEA. Indonesia library will enter the ASEAN Economic Community (AEC) which all the products and experts from specialized foreign countries ASEAN countries free entry into Indonesia and vice versa. So this also needs to look for any people certainly need to be informed, so libraries must be prepared to accommodate it.